A photocatalyst-free visible-light-mediated solvent-switchable route to stilbenes/vinyl sulfones from β-nitrostyrenes and arylazo sulfones. Issue 29 (9th July 2021) - Chawla, Ruchi; Jaiswal, Shefali; Dutta, P. K.; Yadav, Lal Dhar S.
Abstract : A visible-light-mediated solvent-controlled denitrative arylation/sulfonylation of β-nitrostyrenes employing photolabile arylazo sulfones to synthesize trans -stilbenes and ( E )-vinyl sulfones under mild conditions has been developed. Abstract : Photocatalyst-free visible-light-mediated reactions, based on the presence of a visible-light-absorbing functional group in the starting material itself in order to exclude the often costly, hazardous, degradable and difficult to remove or recover photoredox catalysts, have been gaining momentum recently. We have employed this approach to develop a denitrative photocatalyst-free visible-light-mediated protocol for the arylation/sulfonylation of β-nitrostyrenes employing arylazo sulfones (bench-stable photolabile compounds) in a switchable solvent-controlled manner. Arylazo sulfones served as the aryl and sulfonyl radical precursors under blue LED irradiation for the synthesis of trans -stilbenes and ( E )-vinyl sulfones in CH3 CN and dioxane/H2 O 2 : 1, respectively. The absence of any metal, photocatalyst and additive; excellent selectivity ( E -stereochemistry) and solvent-switchability; and the use of visible light and ambient temperature are the prime assets of the developed method. Moreover, we report the first photocatalyst-free visible light-driven route to synthesize stilbenes and vinyl sulfones from readily available β-nitrostyrenes.